Rule of Darā’ and Doubt about Expediency in the Enforcement of Criminal Judgments - Dayani Najaf Abadi, Abdolamir; Tavakoli, Ahamdreza; ShekarchiZadeh, Mohsen; Hadi Mahdavi, Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
The effect of doubt and expediency on the enforcement of criminal judgments has long been considered by the early and late jurisprudents, and contemporary jurists and jurisprudents have also discussed it in their jurisprudential and legal books. The issue of doubt that has been raised in the rule of darā’ is a common rule and is taken from the text and is widely used in criminal judgments, including Hudud (prescribed punishment), Qisas (retaliation in kind), and Ta’zir (discretionary punishment). It is also considered among the rules agreed by the five Islamic religions. Although famous jurisprudents believe that the provisions of this rule can be used in errors of fact (doubt about facts), according to the acceptance of this rule, which is taken from narratives, it can also be applied to errors of law (doubt about law). In criminal law, doubt is sometimes about the legal element, i.e., legislative decree, and sometimes it is about the spiritual element, or actus reus (wrongful act), which is the same as doubt about the realization of crime. The inclusion of the rule has also been accepted in these cases. On the other hand, “expediency” is also effective in enforcing criminal judgments, even Hudud, and can cause delay, change, and even stop the enforcement of the judgment. It seems that error (or doubt) is also effective in the stage of enforcing criminal judgments and can stop the enforcement; that is, execution of a judgment where social justice is not fully implemented is a matter of error (or doubt). Thus, along with the errors of fact and law, we also have probability of mistake and reluctance, doubt of the judge and the accused, probability of repentance, and doubt about the enforcement of judgment, which are a new alternative to errors or doubts. In this study, semantic analysis of doubt and expediency in Islamic jurisprudence and the effect of doubt about expediency on criminal judgments, including Hudud, retaliation in kind, monetary compensation and discretionary punishment, have been addressed through a descriptive-analytical method